2016
DOI: 10.5603/ep.a2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Różnicowanie zmian ogniskowych w wolu guzkowym tarczycy z zastosowaniem nowych technik ultrasonograficznych — doniesienia wstępne

Abstract: Introduction: To evaluate the relative value of technical ultrasound advances in differentiation of thyroid nodules in multinodular goitre. Material and methods:The study included patients with multinodular goitre, who were referred for thyroidectomy. Ultrasound evaluation of suspicious nodules was performed with: improved B-mode (spatial compound imaging and differential tissue harmonics), dedicated mapping of microcalcifications, mapping of the nodule vessels, and strain elastography evaluated qualitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Data from our analysis compared to the original results are as follows: sensitivity 0.875 vs. 0.957 (B-mode) and 0.985 (B-mode + elastography), specificity 0.293 vs. 0.61 (B-mode) and 0.447 (B-mode + elastography), PPV 0.119 vs. 0.06 (B-mode) and 0.016 (B-mode + elastography), NPV 0.956 vs. 0.997 (B-mode) and 0.998 (B-mode + elastography), and diagnostics accuracy 0.35 vs. 0.62 (B-mode) and 0.483 (B-mode + elastography). It was disappointing to find that TIRADS classification with elastography fared worse than classification based on B-mode as presented in Table III and reported previously by Moon et al and Migda et al [15,24]. These authors showed clearly that grey-scale with elastography has poorer results for distinguishing benign from malignant nodules compared to single grey-scale assessment.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Data from our analysis compared to the original results are as follows: sensitivity 0.875 vs. 0.957 (B-mode) and 0.985 (B-mode + elastography), specificity 0.293 vs. 0.61 (B-mode) and 0.447 (B-mode + elastography), PPV 0.119 vs. 0.06 (B-mode) and 0.016 (B-mode + elastography), NPV 0.956 vs. 0.997 (B-mode) and 0.998 (B-mode + elastography), and diagnostics accuracy 0.35 vs. 0.62 (B-mode) and 0.483 (B-mode + elastography). It was disappointing to find that TIRADS classification with elastography fared worse than classification based on B-mode as presented in Table III and reported previously by Moon et al and Migda et al [15,24]. These authors showed clearly that grey-scale with elastography has poorer results for distinguishing benign from malignant nodules compared to single grey-scale assessment.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous ultrasound techniques, such as classic B-mode, Power, and Color Doppler imaging, as well as newer techniques, such as elastography and contrastenhanced ultrasound, have been investigated for their ability to differentiate thyroid nodules. However, recent studies indicate that the most valuable in this regard is B-mode ultrasound [15,[19][20][21][22]. Additionally, grey-scale imaging of focal lesions is simpler and cheaper than newer techniques, which require greater experience, more expensive equipment, and, in cases where microvascularisation is assessed, additional costs associated with the contrast agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation